2007
DOI: 10.3808/jei.200700086
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Riparian Buffer Studies

Abstract: ABSTRACT. Riparian buffers are vegetated areas along water bodies that serve an array of functions, ranging from water quality protection, soil erosion control, to species preservation. The establishment and maintenance of riparian buffers have been an important environmental management practice in the United States since the 1970's. Emerging along with this practice is a body of knowledge about riparian buffers. In this article, over 500 articles published in the past three decades are reviewed, substantiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 169 publications
0
6
0
Order By: Relevance
“…Another best management practice recommended to decrease sediment losses is the establishment of edge-of-field buffer strips and the use of riparian buffer strips along lake or stream banks (Lovell and Sullivan, 2006). Riparian buffers are vegetated areas along the edge of water bodies designed to help decrease runoff and nutrient and soil losses into waterways (Shearer and Xiang, 2007). Riparian buffers have been widely implemented because they are considered key zones to interrupt the flow path from agricultural land to surface waters (Stutter et al, 2012).…”
Section: Long-term Effects Of Grazing Management and Buffermentioning
confidence: 99%
See 1 more Smart Citation
“…Another best management practice recommended to decrease sediment losses is the establishment of edge-of-field buffer strips and the use of riparian buffer strips along lake or stream banks (Lovell and Sullivan, 2006). Riparian buffers are vegetated areas along the edge of water bodies designed to help decrease runoff and nutrient and soil losses into waterways (Shearer and Xiang, 2007). Riparian buffers have been widely implemented because they are considered key zones to interrupt the flow path from agricultural land to surface waters (Stutter et al, 2012).…”
Section: Long-term Effects Of Grazing Management and Buffermentioning
confidence: 99%
“…Riparian buffers have been widely implemented because they are considered key zones to interrupt the flow path from agricultural land to surface waters (Stutter et al, 2012). The vegetative cover can be herbaceous and/or forest, and some studies have shown that a grass–forest combination can be very effective for trapping sediment (Lowrance and Sheridan, 2005; Schultz et al, 2013). A review of riparian buffer studies has indicated that grass buffers and forest buffers separately have approximately equal sediment trapping efficiency (Yuan et al, 2009), but forest buffers have been found to be the most effective for bank stabilization (Kronvang et al, 2012).…”
mentioning
confidence: 99%
“…Comparing the results obtained in this study is challenging as most studies within riparian areas try to identify the most cost-effective buffer width depending on the pollutant load in agricultural systems or constructed wetlands. This is motivated by the fact that land managers do not want to sacrifice more productive land than they have to (Wenger, 1999;Shearer and Xiang, 2007). Consequently, the centre of attention has been on comparing inputs versus outputs of pollutants in runoff through vegetative buffer strips (Schultz et al, 2000;Maillard and Imfeld, 2014).…”
Section: Pollutant Removal Via Sorptionmentioning
confidence: 99%
“…[8] In a recent review on riparian buffer studies, the role of GIS in the parameterization and visualization of hydrological modeling on agricultural buffer restoration was highlighted. [9] On the basis of previous studies, this research further applies RS and GIS technologies to develop a methodological framework for the assessment of riparian buffers in agricultural watershed. The developed framework could be used to evaluate spatial dynamics of farming intensities in riparian buffers by catchments and by buffer sizes, thus providing critical information for land restoration planning.…”
Section: Introductionmentioning
confidence: 99%